Protein C inhibitor regulates both cathepsin L activity and cell-mediated tumor cell migration - Fortenberry, Yolanda M.; Brandal, Stephanie; Bialas, Ryan C.; Church, Frank C. (Biochimica et biophysica acta, 2010)
Protein C inhibitor (PCI) is a plasma serine protease inhibitor (serpin) that regulates several serine proteases in coagulation including thrombin and activated protein C. However, the physiological role of PCI remains under investigation. The cysteine protease, cathepsin L, has a role in many physiological processes including cardiovascular diseases, blood vessel remodeling, and cancer. We found that PCI inhibits cathepsin L with an inhibition rate (k 2) of 3.0 × 10 5 M − 1 s − 1. Whereas, the PCI P1 mutant (R354A) inhibits cathepsin L at rates similar to wild-type PCI, mutating the P2 residue results in a slight decrease in the rate of inhibition. We then assessed the effect of PCI and cathepsin L on the migration of human breast cancer (MDA-MB-231) cells. Cathepsin L was expressed in both the cell lysates and conditioned media of MDA-MB-231 cells. Wound-induced and transwell migration of MDA-MB-231 cells was inhibited by exogenously administered wtPCI and PCI P1 but not PCI P14 mutant. In addition, migration of MDA-MB-231 cells expressing wtPCI was significantly decreased compared to non-expressing MDA-MB-231 cells or MDA-MB-231 cells expressing the PCI P14 mutant. Downregulation of cathepsin L by either a specific cathepsin L inhibitor or siRNA technology also resulted in a decrease in the migration of MDA-MB-231 cells. Overall, our data show that PCI regulates tumor cell migration partly by inhibiting cathepsin L. Consequently, inhibiting cathepsin L by serpins like PCI may be a new pathway of regulating hemostasis, cardiovascular and metastatic diseases.